A Norm-Based Conditional Process Model of the Negative Impact of Optimistic Bias on Self-Protection Behaviors During the COVID-19 Pandemic in Three Chinese Cities - Chen, Sijing; Liu, Jianwei; Hu, Huamin (Frontiers in Psychology, 2021)
Data were collected from 896 participants in three Chinese cities affected by the COVID-19 pandemic to varying degrees through an online survey platform. A conditional process model was then proposed for the impact of optimistic bias on self-protection behaviors during the COVID-19 pandemic from the perspective of social norms. Statistical analysis demonstrates that optimistic bias has a negative impact on self-protection behaviors through message acceptance. Perceived social norms moderate this relationship in the following ways: (1) The higher the perceptions of social norms, the smaller the negative impact of optimistic bias on message acceptance, and the smaller the positive impact of message acceptance on self-protection behaviors. (2) Within a certain range, the higher the perceptions of social norms, the smaller the negative impact, both direct and indirect, of optimistic bias on self-protection behaviors. (3) The direct and indirect effects of optimistic bias on self-protection behaviors become insignificant when perceptions of social norms are very strong. Comparing the data of the three cities shows that higher risk is associated with a stronger role of social norms in moderating the relationship between optimistic bias and self-protection behaviors. The above results suggest that there may be both internal (optimistic bias) and external (social norms) reference points in individual decision-making regarding health behaviors. The theoretical and practical significance of the dual reference points are discussed.